The Relationship Between Wrist Flexibility and Hand Reaction with Drive Stroke in Table Tennis - Awaluddin, Awaluddin; Sahabuddin, Sahabuddin (Sains Global Institut, Indonesia, 2024)
This study aims to determine the relationship between wrist flexion and hand reaction with drive strokes in tennis games. This research is a type of descriptive research. The population of this study is all students of SMP Negeri 40 Makassar with a research sample of 80 male students selected by random sampling. The data analysis technique used is a correlation and regression analysis technique using the SPSS Version 21.00 system at a significant level of 95% or  0.05. Starting from the results of data analysis, this study concludes that: There is a significant relationship between wrist flexion and drive stroke in tennis games, it is proven that the value of ro = 0.845 (P <  0.05); There was a significant relationship between hand reaction and drive stroke in tennis, it was proven that the value of ro = 0.865 (P <  0.05); There was a relationship between wrist flexion and hand reaction with drive strokes in tennis, proving the value of Ro = 0.910 (P <  0.05).